If f(x) = 4x + 12, to find the inverse, reverse the actions of the elements of the function in "reverse" order.
The last thing done is "+ 12", so reverse that first by "- 12"
The previous thing done was "× 4n, so reverse that by "÷ 4", but note that the divide takes precedence over subtract, so the previous step needs to be in brackets.
Thus if the inverse of f(x) is g(x), g(x) = (x - 12) ÷ 4
Chat with our AI personalities
It is: y = -4x+12
8x + 12 = 4x - 4 8x - 4x = -4 - 12 4x = -16 x = -4
23 + 15x - 4x = 1215x - 4x = 12 -2311x = -11x= -1
4[x+3]=4x+12 4x+12=4x+12 it's open.
6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2